Predictors of delayed encephalopathy after acute carbon monoxide poisoning: a literature review - Wang, Yongjing; Zhou, Zunzhen; Zhang, Dailiang; Jiang, Yuan (Frontiers in Medicine, 2025)
Delayed encephalopathy after acute carbon monoxide poisoning (DEACMP) is one of the severe complications that can occur after acute carbon monoxide poisoning (ACOP). The pathogenesis of DEACMP is complex, featuring a delitescence onset and poor prognosis. As a result, many scholars are concentrating on identifying predictors of DEACMP and evaluating their effects, including clinical characteristics, laboratory indicators, neuroelectrophysiology, imaging examination, and genetic susceptibility. However, current identified predictors lack consensus and their clinical application is limited. Therefore, we need to explore new predictors. Exosomes, the smallest extracellular vesicles (EVs) with nano-size, participate in both the physiological and pathological processes of the brain, and the changes in their content can provide valuable information for clinical diagnosis and evaluation of neurodegenerative diseases, suggesting that they may serve as a potential biomarker. However, the practicability of exosomes as biomarkers of DEACMP remains unclear. In the present review, we first introduced the pathogenesis of DEACMP and the currently identified predictors. Then, we also discussed the possibility of exosomes as the biomarkers of DEACMP, aiming to stimulate more attention and discussion on this topic, thereby providing meaningful insights for future research.